Conservative Treatment of Spontaneous Rectus Sheath Hematomas: Single Center Experience and Literature Review - Banu Karapolat; Halil Afsin Tasdelen; Hatice Ayca Ata Korkmaz (Emergency Medicine International)
Introduction. Spontaneous rectus sheath hematoma (SRSH) is characterized by bleeding within the rectus abdominis muscle sheath, one of the rare causes of acute abdominal pain. Early diagnosis is imperative in SRSH to prevent complications and the treatment is usually conservative. We intended to present in this study our experience with SRSH patients with respect to diagnostic evaluation and management of their disease. Materials and Methods. In this retrospective study, 14 patients who had received treatment for SRSH in our clinic between January 2012 and December 2017 were assessed in terms of demographic and clinical characteristics, comorbidities, laboratory parameters, diagnostic approach methods, treatment practices, length of hospital stay, and patient outcomes. Results. The patients consisted of 10 (71.4%) females and 4 males (28.6%). The age of the patients ranged between 47 and 93 with a mean age of 66.5 ± 12.1. Anticoagulant treatments were being administered to 5 (35.7%) patients, antiplatelet treatments to 4 (28.5%) patients, and both anticoagulant and antiplatelet treatments to 4 (28.5%) patients. The most common triggering factor was severe cough and the most common initial symptom acute abdominal pain (71.4%). In physical examinations, the entire patients had generalized abdominal tenderness, 10 (71.4%) voluntary guarding and 7 (50%) a right lower quadrant mass. The diagnosis was confirmed by abdominal ultrasonography and computed tomography. Based on the computed tomography findings, the disease was classified as Type 2 found in 9 (64.3%) patients, Type 1 in 3 (21.4%) patients, and Type 3 in 2 (14.2%) patients. All the patients were treated conservatively. They were hospitalized for 1 to 23 days. There was no mortality. All the patients were followed up between 3 months and 2 years and no recurrence was recorded. Conclusion. Considering the presence of SRSH particularly in older female patients who use anticoagulant drugs and have newly developed an abdominal pain and a palpable mass after coughing spells is the key to make an early and correct diagnosis and to prevent possible morbidity and mortality with an appropriate treatment method.